Evaluation study of the implementation of hospital health promotion - Muhaimin Fansuri; Setiaji, Bambang; Karyus, Aila; Budiati, Endang; Rolia, Eva; Irawan, Hengki (Universitas Islam Negeri Alauddin Makassar, 2024)
There are many obstacles faced in the implementation of health promotion in hospitals. One of the main obstacles is the passive attitude of hospitals that only wait for patients to come without paying attention to the surrounding health aspects, which is an ancient function of hospitals in ancient times that functioned as curative and rehabilitative efforts. The services provided tend to be individual and do not consider the impact on society as a whole. In addition, the lack of competent resources in health promotion is also a problem because hospitals have little or no skilled manpower in this field. The use of purposive sampling in this study aims to find out how the implementation of Hospital Health Promotion that has been carried out by General Ahmad Yani Hospital is in line with the PKRS implementation standards set by Permenkes No. 44 of 2018. The informants used are key informants, main informants, and additional informants. Based on the formulation of the problem and the objectives of the study, the exposure to this data is grouped into four, namely: (1) data exposure regarding the implementation of standard I carried out by hospital employees, (2) implementation of standard II carried out by hospital employees, (3) implementation of standard III carried out by hospital employees, (4) implementation of standard IV carried out by hospital employees, These measures include the formation of a special team responsible for assessing the hospital's Human Resources (HR) and encouraging the hospital's human resources to conduct research related to PKRS. In addition, the hospital is expected to adopt the PKRS concept as stipulated in Permenkes No. 44 of 2018 by involving all relevant stakeholders.